Effect of substrate temperature on the properties of diamond-like carbon deposited by PECVD in methane atmosphere - Sarmid, Suriany; Oeraman, Karim; Ismail, Bakar; Sakrani, Samsudi (2006)
Diamond-like carbon thin films were prepared at different substrate temperatures by using DC·PECVD at 1x10·1Torr in methane atmosphere. The DC-PECVD system was reconstructed for gelling higher substrate temperature up to 560°C. Raman spectroscopy has been used to study the effect of chemical bonding of the films and the deposition rate is studied too. The deposition rate is decreased with the increasing substrate temperature. The Raman main band is due to the lattice vibration of Sp2 bonded carbon atoms (graphite band or G band). If the size of the graphite domains decrease. a low frequencies modulation corresponding to the disorder zone of graphite that corresponding to D peak. The Sp3 bonded carbon increased as the substrate temperature increase from 27°C to 200°C. The result also showed that loIlG ratio decreased with increasing amount of Sp3 fraction as the temperature is increased up to 200°C.